Uji Aktivitas Analgetika Fraksi-Fraksi Ekstrak Etanol Daun Gandarusa (Justicia gendarussaBurm. f) dengan Metode Tail Flick - Rosa Juwita Hesturini; Rina Herowati; Gunawan Pamudji Widodo (Fakultas Farmasi Universitas Setia Budi, 2018)
ABSTRACTGandarusa (Justicia gendarussa Burm. f) is a potential plant as analgetic activities.The aim of the present research was to investigate the analgetic activity with tail flick method onrat models of ethanol extract and the fractions of gandarusa leaf.Partitioned fractinations isolated from ethanolic extract of gandarusaleaves with nheksana,etil asetat and water. Dosage extracts and fractions gandarusa leaf, respectively, are250 mg/kg bw, 500 mg/kg bw, n-hexane fraction of 314 mg/kg bw, the fraction of 41,05 mg/kgbw and water fractions 144,8 mg/kg bw, the negative control group CMC and aspirin 360 mg/kgbw. The results showed the n-heksana fraction has optimal analgesic activity withantinociceptive percentage 94,58% comparable to aspirin.The preliminary phytochemical analisys showed the presence of active phytochemicalsuch as flavonoids, alkaloids, saponins, steroids dan tannins and these compound might beresponsible for analgetic mechanism. The possibility analgetic mechanism of the gandarussa itsstimulate lipomodulin protein biosynthesis which inhibit the action of phospolipase enzimaticthat affecting the enzyme activity arachidonic acid but there is also has gastroprotective activitywith increased mucus production and prevents the release of histamine.